2015
DOI: 10.17219/acem/27566
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hepatitis A in 108 Adult Patients During an Eight-Year Observation in a Single Center in Poland

Abstract: Background. Hepatitis A is related to significant morbidity and occasional mortality. Based on data from the Polish National Institute of Hygiene, from 2000 to 2013 a mean of 213 hepatitis A cases were reported yearly. Objectives. The aim of the study was to assess selected data in adults hospitalized for symptomatic hepatitis A during an eight-year period in a single center in the Wielkopolska Region of Poland. Material and Methods. All the hepatitis A patients hospitalized in the center from 2005 to 2013 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…While viral hepatic infections are an unusual etiology for acute calculous cholecystitis (ACC), most cases have been related to EBV, HAV, and HBV. 6,7,10 HCV is a member of the Flaviviridae family and is characterized by a single positive-strand RNA genome that can be divided into seven genotypes. 16 Acquisition of HCV most often results in chronic infection and inflammation leading to serious liver damage such as cirrhosis and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While viral hepatic infections are an unusual etiology for acute calculous cholecystitis (ACC), most cases have been related to EBV, HAV, and HBV. 6,7,10 HCV is a member of the Flaviviridae family and is characterized by a single positive-strand RNA genome that can be divided into seven genotypes. 16 Acquisition of HCV most often results in chronic infection and inflammation leading to serious liver damage such as cirrhosis and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas ACC is considered a local gallbladder disease process, AAC is typically a manifestation of systemic critical illness. [1][2][3][4][5][6]19 A recent prospective study by Laurila and colleagues 19 analyzing 84 gallbladder tissue samples among patients with AAC reported biliary infiltration into the mucosa and muscular layers, leukocyte arterial margination with nonthrombotic hypoperfusion (ischemia), focal lymphatic dilatation with interstitial edema, and less epithelial degeneration (necrosis) when histologically compared to ACC samples. A microangiography study by Hakala and colleagues 20 among 15 gallbladder samples also reported that nonthrombotic small arterial occlusion was a consistent feature of AAC when compared to ACC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These high prevalences could be related to the source of water supply and sanitation, and individual social characteristics of those who did not change behaviors toward the prevention and awareness of the disease [33,34]. In addition, young adults appear to be the most exposed to the external environment there by exposing them to the virus [35][36][37]. In this study, the prevalence of HAV infection among women living in unsanitary and underserved areas (Peripheral, 90.7%) was higher than women living in serviced areas (Center, 88.3%) ( Table 4).…”
Section: Prevalence Of Hav Antibodies and Risk Factorsmentioning
confidence: 99%
“…5 The disease may also be complicated by extra-hepatic manifestations. 6 On rare occasions, HAV infection results in fulminant disease with case-fatality rates as high as 60%, 2 and patients with chronic liver disease are at increased risk for severe or fulminant disease requiring urgent liver transplantation due to liver failure. The major factors associated with the worst outcomes include age, underlying liver disease and co-infection with other hepatotropic viruses.…”
Section: Introductionmentioning
confidence: 99%